2021
DOI: 10.31389/jltc.74
|View full text |Cite
|
Sign up to set email alerts
|

COVID, Communication and Care Homes: A Staffs’ Perspective of Supporting the Emotional Needs of Families

Abstract: An important part of care home life is the support given to older residents by their families/friends through regular visiting. Social visits to residents by their families ceased in response to the COVID-19 pandemic and residents were confined to their rooms. This paper reports on how care home staff improvised to address this situation during the first wave of the pandemic. It focuses on steps taken to maintain communication between residents and families to support emotional well-being. We undertook in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Conducting sensitive and personal discussions remotely was found to add to the existing emotional toll associated with advance care planning. 30,31,33 Specifically, the reduction of face-to-face contact and non-verbal communication made it harder to share, express and recognise emotions and build trusting relationships. 30,33 Despite the increased emotional toll, care home staff had reduced time due to workload to focus on self-care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conducting sensitive and personal discussions remotely was found to add to the existing emotional toll associated with advance care planning. 30,31,33 Specifically, the reduction of face-to-face contact and non-verbal communication made it harder to share, express and recognise emotions and build trusting relationships. 30,33 Despite the increased emotional toll, care home staff had reduced time due to workload to focus on self-care.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our synthesis suggested that the reality of death and decline brought by COVID-19 encouraged more care home staff, residents and relatives to want to prepare for the end of life, cultivating a more open culture and increased recognition of care planning. 30,31,33 In terms of care home staff, this change was manifested in their triggering of earlier and more frequent discussions with residents and relatives, 33,38 with changed communication patterns more conducive to regular contact between staff and relatives. 31 Furthermore, a change in preference was noted in regard to relatives' and residents' opinions of hospitalisation and intensive care unit use at the end of life.…”
Section: Human Agencymentioning
confidence: 99%
See 3 more Smart Citations